EFFICACY OF LACTUCA SATIVA IN HYPERLIPIDEMIA: A PILOT STUDY - Siva Rami Reddy E, Siva Rami Reddy E; Basavaraj S Adi, Basavaraj S Adi; Arun Kumar Jamadade, Arun Kumar Jamadade (International Journal of Indigenous Herbs and Drugs, 2019)
Aim:Lactuca sativa has anti toxidant, anti inflammatory and anti diabetic activities. In the present pilot study is that efficacy of lactuca sativa in hyperlipidemia. Hyperlipidemia patients meeting the inclusion criteria were randomly assigned in to the treatment and placebo.Methods: 40 all randomized patients in treatment group took lettuce seed capsule (1000 mg, once per day); whereas the patients in placebo group took placebo capsule (once per day) for 12 weeks. The lipid profile, blood pressure, body mass index and liver enzymes of the patients were evaluated at baseline, and after 6 and 12 weeks of the clinical trial.Results: The final results showed that lactuca sativa capsules significantly p value 0.05 improved LDL, HDL, cholesterol, compared to the placebo group. It had no effect on systolic or diastolic blood pressure and the effect on BMI reduction was not significant (P>0.05) compared to placebo. The lettuce showed an inhibitory effect on atorvastatin-induced elevation of hepatic enzymes and possible liver toxicity. No serious side effect was reported for lettuce seed extract administration. Therefore, lettuce seed extract could be considered as a supplement for treatment of dyslipidemia.